2018
DOI: 10.3389/fenvs.2018.00071
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities With On-Farm Research: Total and Soluble Reactive Stream Phosphorus Before and After Implementation of a Cattle-Exclusion, Riparian Buffer

Abstract: Many nutrient mitigation best management practices (BMP) are promoted by state and federal agencies to protect water quality from animal agriculture. The measured effectiveness of these is highly variable in the research literature. Here, we establish pre-and post-BMP monitoring to evaluate the effectiveness of fencing out cattle from the riparian zone on water quality, specifically, phosphorus (P) loads and concentrations. We collected water samples year-round both before and after a cattle exclusion was esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…We simulated daily discharge, soil moisture, snowpack water equivalent, and groundwater storage with a modified version of JoFlo, the lumped model of Archibald et al (2014). This model has previously been applied to evaluate broad patterns of surface runoff (Knighton, Pleiss, et al, 2019) and forest cover change (Singh et al, 2019) across CONUS, as well as in catchment-scale studies of stable water isotope dynamics (Knighton et al, 2017) and nutrient transport (Georgakakos et al, 2018).…”
Section: Rwu Parameter Estimationmentioning
confidence: 99%
“…We simulated daily discharge, soil moisture, snowpack water equivalent, and groundwater storage with a modified version of JoFlo, the lumped model of Archibald et al (2014). This model has previously been applied to evaluate broad patterns of surface runoff (Knighton, Pleiss, et al, 2019) and forest cover change (Singh et al, 2019) across CONUS, as well as in catchment-scale studies of stable water isotope dynamics (Knighton et al, 2017) and nutrient transport (Georgakakos et al, 2018).…”
Section: Rwu Parameter Estimationmentioning
confidence: 99%
“…Within JoFlow, surface runoff is solved via a modified curve number approach, and vadose zone dynamics and ET are determined through the daily Thornthwaite-Mather soil water budget. We selected JoFlow for its low dimensionality and the inclusion of hydrologic processes relevant to our study (Georgakakos, Morris, & Walter, 2018;Knighton, Saia, et al, 2017b;Knighton, Steinschneider, & Walter, et al, 2017a).…”
Section: Hydrological Model Developmentmentioning
confidence: 99%
“…This approach potentially provides further insight into the mechanisms of runoff generation. We note that selection of the sampling ranges of hydrologic parameters is a critical issue in sensitivity analysis, and hydrologic model parameter ranges for this research were selected following other studies utilizing JoFlow (Georgakakos et al, 2018;Knighton, Saia, et al, 2017b;Knighton, Steinschneider, & Walter, et al, 2017a). Further, in order to understand the sensitivity of this analysis to the parameters time-to-peak (Tp, h), a measure of the time between the onset of a precipitation event and discharge peak associated with the event, and percent impervious cover (percent impervious, %), a measure of the proportion of groundcover impervious to water infiltration, we repeated this analysis twice: (a) by increasing the range of Tp to (0, 100) hours, allowing for longer catchment flow paths (see Figures S8 and S9), and (b) by removing percent impervious from the analysis, forcing runoff processes to occur solely as a saturation-excess process (e.g., Schneiderman et al, 2007) (see Figures S10 and S11).…”
Section: Hydrological Model Developmentmentioning
confidence: 99%
“…However, their NRE is reportedly highly variable, ranging from below zero up to almost 100%, depending on many factors such as plantation width, vegetation (plant species used), nutrients considered, input load, climate, local hydrogeological conditions, and the time period after installation (crop maturity and establishment) [16,116,117]. Richardson et al [116] and Georgakakos [118] reviewed the history and performance of fixed-width buffer strips and concluded that despite billions of dollars in investment and 30 years of promotion and implementation on agricultural land worldwide, there has been very little evidence of their efficiency, in particular in P reduction.…”
Section: Nrementioning
confidence: 99%